2018
DOI: 10.1177/0730888418791652
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Work–Life Policies and the Gender Wage Gap in European Workplaces

Abstract: Many organizations in Europe offer work-life policies to enable men and women to combine work with family life. The authors argue that the availability of organizational work-life policies can also reduce gender inequality in wages. The authors test their expectations using the European Sustainable Workforce Survey, with data from 259 organizations and their employees in 9 European countries. Multilevel analyses show that organizations that offer work-life policies have a smaller gender wage gap. Their finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…The findings that flexitime and teleworking may not neccessarily lead to a large negative career outcome is a welcome one. Actually, these arrangements have been shown to reduce women's likelihood of working part-time after childbirth (Chung and Van der Horst 2018b), reduce the motherhood penalty (Fuller and Hirsh 2018;Van der Lippe et al 2018), and potentially increase wage premiums for women especially in the longer run (Langner 2018). Then why despite the stigma and negative career outcomes do women continue to work part-time after becoming mothers?…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings that flexitime and teleworking may not neccessarily lead to a large negative career outcome is a welcome one. Actually, these arrangements have been shown to reduce women's likelihood of working part-time after childbirth (Chung and Van der Horst 2018b), reduce the motherhood penalty (Fuller and Hirsh 2018;Van der Lippe et al 2018), and potentially increase wage premiums for women especially in the longer run (Langner 2018). Then why despite the stigma and negative career outcomes do women continue to work part-time after becoming mothers?…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…1 In fact, there is evidence that flexible working, in particular those that provide workers with more control over their work such as flexitime and teleworking, can help reduce the gender wage gap. This is because these arrangements help women maintain their labour market position and stay in high paying jobs after childbirth (Chung and Van der Horst 2018b;Fuller and Hirsh 2018;Piasna and Plagnol 2017;Van der Lippe et al 2018). To enable better labour market integrations of mothers, the UK government has introduced the right to request flexible working in 2003 for parents of young children.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between flexible working and work–family conflict have different outcomes for men and women, as women are often still more responsible for housework and childcare and spend more time on these chores (Van der Lippe et al 2018 ; and also see the next section). The effect of work role ambiguity on work–family conflict is also different for men and women (Michel et al 2011 ).…”
Section: Summary Of Existing Literature and Their Limitationsmentioning
confidence: 99%
“…However, this is not always the case. Several studies have shown that flexible working may allow women to work longer hours than they would have otherwise after childbirth (Chung and Van der Horst 2018b ) and stay in relatively stressful yet high paying occupations (Fuller and Hirsh 2018 ) and workplaces with flexible working arrangements are those where the gender wage gap is smaller (Van der Lippe et al 2018 ). Thus the picture is rather complex in terms of what flexible working can mean for gender equality.…”
Section: Summary Of Existing Literature and Their Limitationsmentioning
confidence: 99%
“…Similar results have been found by several scholars. Flexible working—again workers’ control over their work—has been shown to help women stay in relatively stressful yet high paying occupations (Fuller & Hirsh, 2018 ), and workplaces with flexible working arrangements are those where the gender wage gap is smaller (Van der Lippe, Van Breeschoten, & Van Hek, 2018 ). In this sense, we need more evidence to see how these rather conflicting directions of impact of flexible working on the gender pay gap act in the longer term for workers.…”
Section: Outcomes Of Family-friendly Arrangements/flexible Workingmentioning
confidence: 99%